Trace element, Nd-Hf-Pb isotope geochemistry, and zircon U-Pb geochronology of the Baskil Dikes (Elazığ, Eastern Türkiye): Tracing Late Cretaceous continental arc magmatism in the Southern Neotethys (vol 86, 126396, 2026) - Sayit, Kaan; Ural, Melek; Koralay, Osman Ersin; Goncuoglu, Mehmet Cemal (Elsevier Gmbh, 2026)
[Abstract Not Available]
Keywords: [Keyword Not Available]